Something is rotten in the State of Denmark. : Simone Aaberg Kaern - Olafur Eliasson - Jens Haaning - Jutte Hoy - Frans Jacobi - Joachim Koester - Jakob Kolding - Peter Land - Ann Lislegaard - Kirsten Ortwed - Christian Schmidt-Rasmussen - Klaus Thejll Jacobsen - Superflex - Rasmus Knud. - Angkjaer Jorgensen, Ulla; Bang Larsen, Lars; Block, René; Gaensheimer, Susanne; Jensen, Knud W. (Kassel : Museum Fridericianum, 1998)
Aaberg, Simone ; Eliasson, Olafur ; Haaning, Jens ; Hoy, Jytte ; Jacobi, Frans ; Koester, Joachim ; Kolding, Jakob ; Land, Peter ; Lislegaard, Ann ; Ortwed, Kirsten ; Schmidt-Rasmussen, Christian ; Thejll Jacobsen, Klaus ; Superflex ; Knud, Rasmus
biog. per kunstenaar
Duits
Something is rotten in the State of Danmark, Museum Fridericianum, Kassel, 12. Juli bis 13. September 1998
boek
Keywords: Denemarken